2017
DOI: 10.1056/nejmoa1709030
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Nivolumab versus Ipilimumab in Resected Stage III or IV Melanoma

Abstract: Among patients undergoing resection of stage IIIB, IIIC, or IV melanoma, adjuvant therapy with nivolumab resulted in significantly longer recurrence-free survival and a lower rate of grade 3 or 4 adverse events than adjuvant therapy with ipilimumab. (Funded by Bristol-Myers Squibb and Ono Pharmaceutical; CheckMate 238 ClinicalTrials.gov number, NCT02388906 ; Eudra-CT number, 2014-002351-26 .).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

36
1,423
5
55

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,887 publications
(1,590 citation statements)
references
References 19 publications
36
1,423
5
55
Order By: Relevance
“…Since that time, there has been a tremendous improvement in our understanding of the molecular and immune biology of melanoma, which has led to the unprecedented introduction and widespread use of a number of effective systemic therapies for patients with advanced disease and in the adjuvant setting. [1][2][3][4][5][6] To facilitate an evidence-based approach and to inform revisions for the 8th edition of the AJCC melanoma staging system, we created a contemporary international melanoma database: the International Melanoma Database and Discovery Platform (IMDDP). 7 Given the recent advances in the clinical management of patients with advanced and unresectable disease, rapidly evolving treatment options for such patients and varying approval for use of these new agents in different parts of the world, the AJCC melanoma expert panel considered that it was inappropriate to include stage IV patients in their initial data analyses of the IMDDP.…”
mentioning
confidence: 99%
“…Since that time, there has been a tremendous improvement in our understanding of the molecular and immune biology of melanoma, which has led to the unprecedented introduction and widespread use of a number of effective systemic therapies for patients with advanced disease and in the adjuvant setting. [1][2][3][4][5][6] To facilitate an evidence-based approach and to inform revisions for the 8th edition of the AJCC melanoma staging system, we created a contemporary international melanoma database: the International Melanoma Database and Discovery Platform (IMDDP). 7 Given the recent advances in the clinical management of patients with advanced and unresectable disease, rapidly evolving treatment options for such patients and varying approval for use of these new agents in different parts of the world, the AJCC melanoma expert panel considered that it was inappropriate to include stage IV patients in their initial data analyses of the IMDDP.…”
mentioning
confidence: 99%
“…As ipilimumab was compared with placebo in EORTC 18071, the results of a US Intergroup Phase III trial, ECOG 1609, comparing ipilimumab with high-dose interferon, will be of key importance in future decision-making regarding adjuvant therapy. More recently, results of CheckMate 238 showed improved RFS at 18 months with 1 year of anti-PD1 therapy when compared with ipilimumab (66.4 vs 52.7%, respectively) in patients with resected Stage IIIB, IIIC or IV melanoma [15]. Anti-PD1 therapy appears to have an improved therapeutic index over any previous adjuvant systemic therapy; while longer follow-up is required to demonstrate survival impact and results of trials comparing checkpoint blockade to interferon are awaited, the CheckMate 238 trial is widely considered to have established a new standard of care for these patients [26].…”
Section: Discussionmentioning
confidence: 99%
“…This is reflected in the current NCCN guidelines [12]. Recent landmark trials have shown promise in the adjuvant use of CTLA4-blockade [13,14] and anti-PD therapy [15]; however, reports of severe toxicity warrant careful patient selection and no prospective trial has yet shown a survival benefit compared with interferon. Some contemporary clinical trials continue to use adjuvant interferon as the comparator arm, while others do not.…”
mentioning
confidence: 99%
“…5 Nivolumab had a statistically significant improved recurrence-free survival as compared with ipilimumab with the median not reached in those receiving nivolumab (HR 0.65, 97.56% CI 0.51 to 0.83) . 6 Additionally, nivolumab therapy exhibited lower toxicity. Pembrolizumab also resulted in a significant improvement in recurrence-free survival as compared with placebo with the median not reached (HR 0.57, 98.4% CI 0.43 to 0.74) .…”
Section: Case Presentationmentioning
confidence: 99%